NF-kappaB-dependent lymphoid enhancer co-option promotes renal carcinoma metastasis - Rodrigues, Paulo (Cancer Discov, 2018)
Metastases, the spread of cancer cells to distant organs, cause the majority of cancer-related deaths. Few metastasis-specific driver mutations have been identified, suggesting aberrant gene regulation as a source of metastatic traits. However, how metastatic gene expression programs arise is poorly understood. Here, using human-derived metastasis models of renal cancer, we identify transcriptional enhancers that promote metastatic carcinoma progression. Specific enhancers and enhancer clusters are activated in metastatic cancer cell populations and the associated gene expression patterns are predictive of poor patient outcome in clinical samples. We find that the renal cancer metastasis-associated enhancer complement consists of multiple co-activated tissue-specific enhancer modules. Specifically, we identify and functionally characterize a co-regulatory enhancer cluster, activated by the renal cancer driver HIF2A and an NF-kappaB-driven lymphoid element, as a mediator of metastasis in vivo. We conclude that oncogenic pathways can acquire metastatic phenotypes through cross-lineage co-option of physiological epigenetic enhancer states.